A new cause of 'non-responsiveness' in coeliac disease?. Issue 894 (1st April 2000) - Jennings, J S R; Wyatt, J I; Howdle, P D
Abstract : A 42 year old man presented with gluten-responsive coeliac disease and secondary pancreatic insufficiency. Subsequently his symptoms relapsed and repeat small intestinal biopsy showed villous atrophy and infiltration by leukaemic cells, despite continuation of a gluten-free diet. Serious causes of relapse and non-responsiveness in coeliac disease include enteropathy-associated T-cell lymphoma, ulcerative jejunitis and an end-stage hypoplastic mucosa. This is the first report of non-responsiveness due to infiltration by leukaemia.